Diversifikasi Aset, Risiko Bank, Ukuran Bank, dan Likuiditas Bank terhadap Efisiensi Bank Syariah di Indonesia - Anggraeni Anggraeni; Iik Arie Saputri (Journal of Business & Banking, 2020)
There are some factors that affect the banks’ efficiency and therefore, it is important to do research in relation to analyze those factors. The efficiency of the banking industry is required. The purpose of this study is to examine the effect of asset diversification, bank risk, bank size, and bank liquidity on the efficiency of sharia banks using Stochastic Frontier Analysis (SFA). The sample of this research is Sharia Commercial Bank, in Indonesia, which has been registered in OJK for the 2014-2018 period. The data were analyzed by using descriptive and statistical analysis with Frontier 4.1. The results showed that asset diversification, bank risk, and bank liquidity had a negative effect on efficiency. On the contrary, Total Assets has a positive effect on Efficiency. It is recommended that the banks should minimize their risk in order to increase efficiency as well as not to diversify their assets.